Identification of the Common Origins of Osteoclasts, Macrophages, and Dendritic Cells in Human Hematopoiesis - Xiao, Yanling; Zijl, Sebastiaan; Wang, Liqin; de Groot, Daniel C.; van Tol, Maarten J.; Lankester, Arjan C.; Borst, Jannie (Stem cell reports, 2015)
Osteoclasts (OCs) originate from the myeloid cell lineage, but the successive steps in their lineage commitment are ill-defined, especially in humans. To clarify OC origin, we sorted cell populations from pediatric bone marrow (BM) by flow cytometry and assessed their differentiation potential in vitro. Within the CD11b−CD34+c-KIT+ BM cell population, OC-differentiation potential was restricted to FLT3+ cells and enriched in an IL3 receptor (R)αhigh subset that constituted less than 0.5% of total BM. These IL3Rαhigh cells also generated macrophages (MΦs) and dendritic cells (DCs) but lacked granulocyte (GR)-differentiation potential, as demonstrated at the clonal level. The IL3Rαlow subset was re-defined as common progenitor of GR, MΦ, OC, and DC (GMODP) and gave rise to the IL3Rαhigh subset that was identified as common progenitor of MΦ, OC, and DC (MODP). Unbiased transcriptome analysis of CD11b−CD34+c-KIT+FLT3+ IL3Rαlow and IL3Rαhigh subsets corroborated our definitions of the GMODP and MODP and their developmental relationship. [Display omitted] •CD34+c-Kit+Flt3+ IL3Rαhigh phenotype identifies human MΦ/OC/DC progenitor (MODP)•CD34+c-Kit+Flt3+ IL3Rαlow phenotype identifies GMODP, oligopotent for GR/MΦ/OC/DC•CD34+c-Kit+Flt3+ IL3Rαlow GMODP is upstream of CD34+c-Kit+Flt3+ IL3Rαhigh MODP•Transcriptome analysis supports definition and relationship of GMODP and MODP In this article, Borst, Xiao, and colleagues identify two hierarchically related hematopoietic progenitors in the human bone marrow that can give rise to osteoclasts, the cells that can resorb bone and are involved in various diseases. They show that osteoclasts share their developmental origin with macrophages and dendritic cells that have important immune regulatory functions.